Relationship between Indoor and Outdoor Particulate Matter Concentrations in Japan - Satoshi Nakai; Kenji Tamura (Asian Journal of Atmospheric Environment, 2008)
We briefly show the results of indoor and personal PM2.5 measurements in an epidemiologic study designed to evaluate the health risks of ambient PM2.5 in Japan and the relationship between indoor and outdoor PM concentrations. The impact of indoor and outdoor PM pollution on health is described based on one morbidity study. The results of other studies on indoor PM2.5 measurements are also described.